Hypouricemic Activity of Pentopetia Androsaemifolia Decne. (Apocynaceae) Hydro Alcoholic Extract in Mice - P., Randrianavony; A.M., Reboza; N., Quansah; F., Randimbivololona (European Scientific Journal, ESJ, 2017)
The aim of this work was to investigate the uricemic and uricosuric activity of the hydro alcoholic extract of Pentopetia androsaemifolia in experimentally induced hyperuricemic mice. Hyperuricemia was induced in the mice by intraperitoneal injection of potassium oxonate. Oral administration of the extract at doses 50 to 200 mg/kg reduce hyperuricemia from 218.78 ± 7.50 to 72.29 ± 16.88 mg/l (P< 0. 05). The same doses of 50 to 200 mg/kg of the extract also reduce uricosuria from 125.4 ± 4.4 to 70 ± 12.6 mg/l (p< 0.05). A direct correlation exists between plasma uric acid concentration and urine uric acid concentration (r = 0.99). The hypouricemic activity of the extract could be due to xanthine oxidase inhibition by the flavonoids present in the extract.